Nostalgický chronotop pražského tanga: Předběžné obrysy - Gotlib, Matvei (Lidé města, 2021)
This article deals with the study of the Prague tango as a nostalgic practice. It presents the fragments and the findings from the ethnography that the author has been carrying out at the tango parties in Prague since autumn 2019. Emphasis is put on the forms of nostalgia, but not on its objects. The ethnography is based on the theory of body techniques by Marcel Mauss and the conception of dance resources by Susan Lee Foster. Kinaesthetic empathy – a methodology of movement observation – helps describe the narratives that the dancing couples create. as Also, Bakhtin’s concept of chronotopes is used to interpret the collected data. The article covers the Prague tango scene from 2018 to the present. One tango party and narratives of two dancing couples are described in detail. At this time, we can describe five forms (or techniques) of nostalgia in the Prague tango community. These include the ironic use of the vintage attributes of tango, creating and distributing romanticized stories related to tango, unconventional behaviour that helps local tango dancers escape from the normalized reality of the contemporary city, the specific way of listening to old music, and the polyphony of the dancing narratives. The study to which this paper is devoted to should become an example of how modern urban citizens can create new ways of gathering and feel an emotionally meaningful experience.